The Influence on Body Movement on Musical Sense-Making in Primary School Children: a Multi Modal Approach in Music Education - Fortuna, Sandra (Ghent, 2021)
As increasingly confirmed within the paradigm of embodied music cognition, the body shapes the way listeners perceive and make sense of music. Accordingly, this Ph.D research project aims to understand the role of body movement on children’s musical sense-making through two empirical studies setup in an educational ecological setting of primary school. In both studies, the children’s graphical representations of the music and their verbal explanations of the drawings were used to probe children’s musical sense-making. The first study investigated how and in what way a verbal vs. bodily interaction with the music influences the children musical sense-making. Results offer relevant insights into the role of body movement to enhance the identification of more musical features and their temporal organization. Based on the findings of the first study, a second study was carried out to investigate the influence of different qualities (discrete vs. continuous movements) of bodily interactions with music on children’ music meaning formation. Findings of the second study show that based on the quality of movement interaction the children changed the categories of visual representations, arousal, and number of voices of the music described. At a meta- perspective level, the adoption of a multimodal approach (e.g., bodily, visual, and verbal) emerged to be an effective mean to enhance a deeper music understanding. In addition, body movement appears to be a viable way to foster a creative listening through creative navigation of the musical affordance landscape.
Thesis submitted to fulfill the requirements for the degree of Doctor of Art Sciences, Ghent University, Faculty of Arts and Philosophy, Department of Art, Music and Theatre Studies
Keywords: Music education; Motion